인공지능 챗봇 서비스의 수용태도에 미치는 영향요인 분석 : 서비스 가치 매개효과 중심으로 - 김윤경(Yoon-Gyung Kim) (한국콘텐츠학회 논문지, 22(2), 2022)
In this study, it was necessary to examine consumer acceptance attitudes from an in-depth and multifaceted perspective at a time when the need for chatbot services in various industrial fields is increasing and being activated in earnest. Accordingly, this study conducted a structural equation model to examine not only the structural relationship between ease, usefulness, and playfulness among the main functions of chatbot services and their acceptance attitudes, but also whether there is a mediating effect of service value in the relationship. As a result of the main study of this study, it was identified that the relationship between the ease, usefulness, and playfulness factors, which are the main functional sub-factors of the chatbot service, and their acceptance attitude and service value had a statistically static influence relationship. Based on these research results, the main research conclusions suggest that when companies in various fields provide chatbot services in the future, it is necessary to clearly determine the influencing factors that can affect the chatbot service acceptance attitude and provide these services. Through this, it is expected that the AI chatbot service will strengthen communication with consumers and establish itself as a customized and personalized counseling service. 본 연구는 이제 본격적으로 다양한 산업분야에서 챗봇 서비스의 필요성이 증대되고, 활성화되고 있는 시점에 이에 관한 소비자 수용태도를 심층적이고, 다각적인 시각으로 살펴볼 필요성이 있었다. 이에 따라 본 연구는 챗봇 서비스의 주요 기능 중 용이성, 유용성, 유희성 요인과 이의 수용태도 간의 구조적 관계뿐만 아니라, 그 관계에서 서비스 가치의 매개효과가 있는지를 살펴보기 위하여 구조방정식 모형을 실시하였다. 본 연구의 주요 연구결과, 챗봇 서비스의 주요 기능 하위 요인인 용이성, 유용성, 유희성 요인과 이의 수용태도 및 서비스 가치 간의 관계가 통계적으로 정적인 영향 관계가 있음을 파악하였다. 이러한 연구 결과를 토대로 주요 연구 결론을 파악해 보면, 향후 다양한 분야의 기업에서 챗봇 서비스를 제공할 때 챗봇 서비스 수용태도에 미칠 수 있는 영향요인을 명확히 판단하여 이의 서비스 제공이 필요함을 시사하였다. 이를 통해 인공지능 챗봇 서비스에서 소비자와의 소통을 강화하고 맞춤형 개별화 상담 서비스로서 자리매김할 수 있기를 기대한다.